Survival and clinicopathological significance of PYCR1 expression in cancer: A meta-analysis - Li, Yue; Xu, Jiahuan; Bao, Pengchen; Wei, Zhijing; Pan, Lei; Zhou, Jiawei; Wang, Wei (Frontiers in Oncology, 2022)
Background: Proline metabolism is closely related to the occurrence and development of cancer. Δ1-pyrroline-5-carboxylate reductase (PYCR) is the last enzyme in proline biosynthesis. As one of the types, PYCR1 takes part in the throughout process of the growth, invasion and drug resistance of cancer cells. This study investigated PYCR1 expressions in cancers, together with the relationship to clinical prognosis. Methods: A thorough database searching was performed in PubMed, EMBASE and the Cochrane Library. RevMan5.3 software was performed for statistical analysis. Results: 8 articles and 728 cancer patients were enrolled. Cancer types include lung, stomach, pancreatic ductal adenocarcinoma, hepatocellular carcinoma, and renal cell carcinoma. The meta-analysis results showed that the expression of PYCR1 was higher in the clinical stage III-IV group than that in the I-II group (OR=1.67, 95%CI: 1.03-2.71), higher in the lymph node metastasis group than the non-lymph node metastasis group (OR=1.57, 95%CI: 1.06-2.33), and higher in the distant metastasis group than the non-distant metastasis group (OR=3.46, 95%CI: 1.64-7.29). However, there was no statistical difference in PYCR1 expression between different tumor sizes (OR=1.50, 95%CI: 0.89-2.53) and degrees of differentiation (OR=0.82, 95% CI: 0.54-1.24 ). Conclusion: PYCR1 had a high expression in various cancers and was associated with cancer volume and metastasis. The higher the PYCR1 expression was, the poorer the cancer prognosis was. The molecular events and biological processes mediated by PYCR1 might be the underlying mechanisms of metastasis.